Aligning Vocational Curriculum with Industry Needs: A Case Study of Electrical Power Installation Engineering Education - Lukman Hakim; Dinar Ayu Tasya’; Asep Kurniawan (Al-Qalam Institue, 2026)
This study examined the implementation and industry alignment of the Electrical Power Installation Engineering curriculum and its translation into competencies. Vocational education must respond to technological change, workplace standards, and demands for technical and transversal skills. However, curriculum relevance is often constrained by outdated equipment, uneven teacher competence, and limited industry engagement. This qualitative study used an embedded single-case design. Data were collected through interviews, observations, and document analysis, then examined using reflexive thematic analysis and triangulation. Findings showed that curriculum implementation followed a cycle of planning, synchronization, implementation, evaluation, and improvement. Industry partners contributed to competency identification, placements, internships, Teaching Factory activities, safety procedures, and assessment. Teaching Factory strengthened links between theory and authentic work practices. Supporting factors included competent teachers, school support, partnerships, and facilities. Key barriers were limited industry-standard equipment, uneven technological competence, unfavourable student-to-equipment ratios, and restricted partnerships. Curriculum implementation improved technical skills, discipline, teamwork, communication, safety awareness, adaptability, and job readiness. These findings imply that vocational curriculum reform must integrate curriculum, infrastructure, teachers, and industry collaboration. They provide a practical framework for evidence-based curriculum improvement.